Developing professionalism from within and outside: Reflections of editors of the Journal of Student Affairs in Africa at 10 years (Journal of Student Affairs in Africa, 2023)
The Journal of Student Affairs in Africa (JSAA) was founded in 2013 with the aim to contribute to professionalizing Student Affairs in Africa. The 10th anniversary of the journal is a good occasion to ask in what ways the editors of the journal think they have contributed to achieving this aim, and what their vision for the future of such contribution is? Using four reflective accounts of six editors of the journal, this article analyses the editors’ reflections on their professional pathways and the role the journal played in them; how they contribute to the professional development of their emerging and established peers by means of their editorship; the challenges they encounter and lessons they have learned; and the visions they have for the future of the journal. By applying Evett’s notions of professionalism, the article shows different types of professionalism signified in the reflective accounts. It finds that the agency of the editors combines standards, ethics, and operating procedures of publishing ‘from outside’ with principles and commitments indigenous to African Student Affairs. In this regard, the JSAA-led professionalization process combines both elements of professionalism ‘from within’ and ‘from outside’. It further highlights commitments of the editors to wellbeing (of students, staff, and communities), professional development and ‘excellence’, deliberate inclusivity and social justice, and a focus on relevance in the African Student Affairs context.
Keywords: scholarship of practice; publishing; Higher Education; professional development; professionalism; professionalisation; academic affairs; reflective practice